2018
DOI: 10.5994/jei.14.3.117
|View full text |Cite
|
Sign up to set email alerts
|

Ritme aktivitas penerbangan harian Tetragonula laeviceps (Smith) (Hymenoptera: Apidae) di Bogor

Abstract: Tetragonula laeviceps (Smith) adalah salah satu spesies lebah tak bersengat yang paling umum dijumpai di Indonesia. Namun demikian, tidak banyak publikasi tersedia tentang ritme aktivitas penerbangan T. laeviceps. Penelitian ini bertujuan mengkaji aktivitas penerbangan T. laeviceps dalam kaitannya dengan waktu harian dan berbagai unsur cuaca. Tiga koloni diamati setiap jam selama 5 menit dari pukul 06:00 hingga 18:00 WIB. Pengamatan meliputi banyaknya T. laeviceps yang keluar sarang, masuk sarang, memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…This study showed that imidacloprid and fipronil treatment could affect the activities of T. laeviceps and the average leave-return bees after treatment were below 10 individuals with no visiting activity. The activity of T. laeviceps bee starts at 08.00 am to 05.00 pm, and the peak of flying activity occurs at 11.00 am-01.00 pm, with an average number of leave-return bees reaching 60 individuals within 5 minutes (Yustia et al 2017). The bee's activity in the profenofos and control plots continued to increase with increasing observation time and the number of flowers.…”
Section: Discussionmentioning
confidence: 94%
“…This study showed that imidacloprid and fipronil treatment could affect the activities of T. laeviceps and the average leave-return bees after treatment were below 10 individuals with no visiting activity. The activity of T. laeviceps bee starts at 08.00 am to 05.00 pm, and the peak of flying activity occurs at 11.00 am-01.00 pm, with an average number of leave-return bees reaching 60 individuals within 5 minutes (Yustia et al 2017). The bee's activity in the profenofos and control plots continued to increase with increasing observation time and the number of flowers.…”
Section: Discussionmentioning
confidence: 94%
“…Spesies lebah tersebut mulai beraktivitas pada suhu 22-23°C (pagi hari) yang puncak aktivitasnya pada suhu 26-28°C (siang hari) dengan kelembapan sekitar 55-88% (Salatnaya et al 2020). Penelitian Yustia et al (2017) juga menyebutkan puncak aktivitas lebah tanpa sengat pada suhu 34,71°C. Jenis tanah di Kota Depok terbagi menjadi tanah aluvial yang umumnya berada di jalur sungai dengan tingkat kesuburan sedang-tinggi dan tanah latosol yang memiliki tingkat kesuburan rendah dan rentan terhadap erosi.…”
Section: Hasil Dan Pembahasan Karakteristik Ekologis Dan Permukiman K...unclassified